Funciones básicas en el aprendizaje de la lectoescritura en la Unidad Educativa Cristiana ¨Nazareno¨ - Calderón Villa, Vanessa Gabriela (2023)
The objective of this research project was to determine the relationship of the essential functions in the learning of reading and writing in the students of Unidad Educativa Cristiana "Nazareno"; to establish the level of development of the essential functions and the learning capacity in reading and writing, finally to analyze their relationship. Concerning the methodology, the research has a qualitative-quantitative, descriptive, and so correlational which corresponds to a cross-sectional study; In data collection, the level of development of essential functions was evaluated in a total of 50 students in the first and second years of GBE, using the psychometric technique with the application of the essential functions test, designed to assess 16 areas in children from 5 to 8 years of age, which allow determining whether or not they have a good development, On the other hand, the learning capacity for reading and writing was determined in a total of 25 students in the second year of GBE, through the application of the author's reading and writing test (Olea, 1977), designed for children of average intelligence who have received basic instruction for at least one year. The results show a close relationship between the variables since the second-year students to whom both instruments were applied show difficulties in learning to read and write because they need better development in specific areas such as orientation, laterality, rhythm, memory, and attention.